LAURACEAE - A. J. G. H. KOSTERMANS (Research Center for Biology, 1957)
An attempt has been made at a classification of the Lauraceae, into taxa down to the rank of subgenus. The characters and their taxonomic value are discussed amply. A system of the family and keys are given. Two subfamilies, viz Lauroideae and Cassythoideae, are recognized; several new tribes, subtribes and subgenera have been described. The accepted genera, 31 in number, are surveyed, with synonyms, typification, description, and particulars. Additional notes to